(untitled) (LACCEI, 2024)
Currently, SMEs are unable to meet the needs of customers, presenting problems for the delivery of complete orders on time. Based on an analysis of continuous improvement tools and integration of change management within the organization, a new production management model is proposed that manages to reduce delivery times This model uses tools such as: DDMRP, 5S, JIDOKA, TPM and integrates change management with the Kotter model as a base. The proposed model was carried out in a pilot test of an SME in the textile and clothing sector, obtaining as results: an increase in Total (IF) and inventory precision of 87.77% and 95% respectively in addition to the reduction of defective products by up to 2%.